Optimization of Cassava Flour Cookies Characteristics Using Response Surface Methodology - Rompis, Patricia Febriani; Sarofa, Ulya; Munarko, Hadi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
The purpose of this study was to determine the optimal composition of fat (butter-margarine) and cornstarch for the physicochemical properties (hardness, water content, starch content, and fat content) of cassava flour cookies using Response Surface Methodology (RSM). Additionally, this study aimed to evaluate the physicochemical characteristics of the optimized cassava flour cookies. The research employed RSM with a Central Composite Design (CCD) approach involving the fat composition (a mixture of butter and margarine) and cornstarch. 13 treatment combinations were generated and analyzed using Design Expert 13 software. The results showed that adding fat significantly influenced all responses. At the same time, cornstarch addition significantly affected hardness, water content, and starch content but did not significantly affect fat content. The optimal formulation was determined to contain 65% fat and 20% cornstarch, achieving the highest desirability value of 0.9490. The physicochemical parameters of the optimized cassava flour cookies were as follows: hardness (5.44 N), water content (4.54%), starch content (36.95%), fat content (34.91%), ash content (0.58%), protein content (8.13%), carbohydrate content (51.85%), and dietary fiber (7.78%). Contribution to Sustainable Development Goals (SDGs) SDG 2: Zero hungerSDG 3: Good Health and Well-BeingSDG 8: Decent Work and Economic Growth SDG 9: Industry, Innovation, and Infrastructure SDG 12: Responsible Consumption and Production SDG 15: Life on Land